2020
DOI: 10.1111/1748-8583.12333
|View full text |Cite
|
Sign up to set email alerts
|

Unpaid family caregiving responsibilities, employee job tasks and work‐family conflict: A cross‐cultural study

Abstract: Employment is often undertaken simultaneous with providing unpaid care for an elderly or disabled family member. These dual responsibilities can create substantial inter-role conflict. The current study considers how these roles affect work-family conflict by examining: (i) the process which the gender of employees with caregiving responsibilities shapes work-family conflict and (ii) whether this effect of employee gender is moderated by the societal level of gender egalitarianism. Data were collected from emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Evidence nonetheless seems to suggest that institutional supportsor the lack thereofcould have profound effects on an individual's capacity to take on caregiving while pursuing their educational goals. Even among the literature reviewed herein, findings suggest that access to institutional resources to mitigate caregiver strain, like child care, may be critical for caregiver wellbeing (Calarco et al, 2021); that governmental provisions of community-based care programs could support caregivers' participation in the workforce, all while more than offsetting program costs (Schofield et al, 2019); and that in nations with greater institutional supports, such supports as currently designed may still be insufficient to equalize otherwise gender binary caregiving norms (Bainbridge et al, 2021). Indeed, this literature names that such institutional supports cannot assume uniformity across experiences of caregiving, and must reflect the varying needs of both caregivers and recipients of care (Peacock et al, 2020).…”
Section: Structural Supports For Caregivingmentioning
confidence: 90%
“…Evidence nonetheless seems to suggest that institutional supportsor the lack thereofcould have profound effects on an individual's capacity to take on caregiving while pursuing their educational goals. Even among the literature reviewed herein, findings suggest that access to institutional resources to mitigate caregiver strain, like child care, may be critical for caregiver wellbeing (Calarco et al, 2021); that governmental provisions of community-based care programs could support caregivers' participation in the workforce, all while more than offsetting program costs (Schofield et al, 2019); and that in nations with greater institutional supports, such supports as currently designed may still be insufficient to equalize otherwise gender binary caregiving norms (Bainbridge et al, 2021). Indeed, this literature names that such institutional supports cannot assume uniformity across experiences of caregiving, and must reflect the varying needs of both caregivers and recipients of care (Peacock et al, 2020).…”
Section: Structural Supports For Caregivingmentioning
confidence: 90%
“…There are reports mentioned that female employees are mainly responsible for domestic chores, and family caring than males (Doble & Supriya, 2010;Bainbridge, Palm, & Fong, 2020). Findings from a study by Bainbridge et al (2020) show that caregiving was found to have more frequency on female employees compared with men, which leads to work-family conflict. In other words, female workers suffer from role conflicts more than males in terms of balanced work and life (Milliken, Kneeland, & Flynn, 2020).…”
Section: Introductionmentioning
confidence: 99%
“… 14 The burden of attending to demands in the family domain is commonly shouldered by women, 15 a division highly influenced by social and cultural expectations of gender roles in the family, especially in less gender-egalitarian cultures. 16 As female health professionals carry more family caregiving responsibilities, personal resources (eg, time and energy) for work opportunities that are beneficial to their career development are sapped. 14 17 …”
Section: Introductionmentioning
confidence: 99%
“…Demanding life events (eg, marriage, pregnancy, childbirth) and family caregiving duties (eg, caring for young children and/or family members with chronic illness(es)) often coincide with these career stages, with many women lacking resources at work and home to manage demands from both work and life domains 14. The burden of attending to demands in the family domain is commonly shouldered by women,15 a division highly influenced by social and cultural expectations of gender roles in the family, especially in less gender-egalitarian cultures 16. As female health professionals carry more family caregiving responsibilities, personal resources (eg, time and energy) for work opportunities that are beneficial to their career development are sapped 14 17…”
Section: Introductionmentioning
confidence: 99%